Enhancing mechanical properties of low plasticity soil through coal and silica fume stabilization - Muhammad Waleed; Fahad Alshawmar (Scientific Reports)
Abstract Low-plasticity soils, characterized by low plasticity and high sand content, present challenges in engineering projects due to their inadequate strength and stability. This study evaluates the comparative effects of coal waste and silica fume as stabilizers to improve the mechanical properties of silty soils. Key parameters such as liquid limit (LL), plastic limit (PL), plasticity index (PI), maximum dry density (MDD), unconfined compressive strength (UCS), and shear strength were assessed through laboratory experiments with varying stabilizer proportions (3–12%). Results showed that silica fume increased the LL of Tarnol soil by 36% and reduced its PI, while coal waste improved the LL of Chaklala soil by 48%, also reducing its PI. Both stabilizers decreased MDD and increased optimum moisture content (OMC). Notably, UCS increased by 77% in Tarnol soil with 12% silica fume and by 83% in Chaklala soil with 12% coal waste after 28 days of curing. Coal waste improved the cohesion of Chaklala soil by a factor of 1.29 and its internal friction angle by 1.04, while silica fume enhanced Tarnol soil cohesion by 1.35 and its internal friction angle by 1.032. These findings demonstrate the potential of coal waste and silica fume as cost-effective, sustainable stabilizers for improving the geotechnical performance of low-plasticity soils. The study contributes valuable insights into using industrial by-products for soil stabilization, offering practical applications for enhancing soil strength and stability in construction and infrastructure projects.